2010
DOI: 10.2478/v10183-010-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on the behaviour of the Antarctic sea star Odontaster validus

Abstract: Many Antarctic marine benthic invertebrates are adapted to specific environ− mental conditions (e.g. low stable temperatures, high salinity and oxygen content). Changes caused by global climatic shifts can be expected to have significant impact on their physiol− ogy and distribution. Odontaster validus, an ubiquitous, omnivorous sea star is one of the "keystone species" in the Antarctic benthic communities. Laboratory experiments were car− ried out to study the effect of temperature rise (from 0 to 5°C) on som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Populations from the more thermally variable sub-Antarctic island of South Georgia (−1 to + 5°C; Barnes et al 2006) had a greater physiological plasticity of mitochondrial densities and key enzymes, in response to long-term elevated temperature than those from Marguerite Bay ), but reduced acute temperature limits. The acute summer temperature limits of righting and feeding in O. validus at Admiralty Bay, King George Island, on the north-western Antarctic Peninsula (62°S) were also lower than those of Rothera and McMurdo populations (4 to 5°C; Kidawa et al 2010). Methodological differences between Kidawa et al (2010) and both Peck et al (2008) and the current study make it difficult to compare results, as the rate of warming and the magnitude and duration of exposure to elevated temperature all markedly affect the thermal limits of ectotherms (Terblanche et al 2007, Nguyen et al 2011).…”
Section: Geographic Differencesmentioning
confidence: 82%
See 1 more Smart Citation
“…Populations from the more thermally variable sub-Antarctic island of South Georgia (−1 to + 5°C; Barnes et al 2006) had a greater physiological plasticity of mitochondrial densities and key enzymes, in response to long-term elevated temperature than those from Marguerite Bay ), but reduced acute temperature limits. The acute summer temperature limits of righting and feeding in O. validus at Admiralty Bay, King George Island, on the north-western Antarctic Peninsula (62°S) were also lower than those of Rothera and McMurdo populations (4 to 5°C; Kidawa et al 2010). Methodological differences between Kidawa et al (2010) and both Peck et al (2008) and the current study make it difficult to compare results, as the rate of warming and the magnitude and duration of exposure to elevated temperature all markedly affect the thermal limits of ectotherms (Terblanche et al 2007, Nguyen et al 2011).…”
Section: Geographic Differencesmentioning
confidence: 82%
“…The acute summer temperature limits of righting and feeding in O. validus at Admiralty Bay, King George Island, on the north-western Antarctic Peninsula (62°S) were also lower than those of Rothera and McMurdo populations (4 to 5°C; Kidawa et al 2010). Methodological differences between Kidawa et al (2010) and both Peck et al (2008) and the current study make it difficult to compare results, as the rate of warming and the magnitude and duration of exposure to elevated temperature all markedly affect the thermal limits of ectotherms (Terblanche et al 2007, Nguyen et al 2011). In our study there was also an indication that at 11°C, close to the upper limit for righting in Odo ntaster validus, there was a trade-off between turning speed and turning ability between the 2 locations.…”
Section: Geographic Differencesmentioning
confidence: 82%
“…V Mov increased with temperature at pH T 7.9 and pH T 7.7. Enhanced locomotion and activity have been observed in response to warming (Kidawa, Potocka, & Janecki, 2010;Pewsey, 2004;Young, Peck, & Matheson, 2006) and acidification (Cripps et al, 2011;Manríquez et al, 2013;Nilsson et al, 2012;Spady, Watson, Chase, & Munday, 2014), but there is a poor understanding about the effects of combined stressors. As with the echinoid Loxechinus albus (Manríquez et al, 2017), our results revealed positive synergistic effects of OW and OA, since sea urchins were driven to adopt a riskier behavior by moving faster despite the hydrodynamic stress.…”
Section: Escaping Strategymentioning
confidence: 99%
“…For example predation rate of the polar starfish Odontaster validus is compromised by high‐temperature stress (Peck et al . ; Kidawa, Potocka & Janecki ). Temperate regions routinely undergo wide temperature oscillations, due to seasonal cycles and temperature anomalies (Miller et al .…”
Section: Introductionmentioning
confidence: 99%
“…Duggins 1983;Lafferty 2004;Eckert 2007;Bonaviri et al 2009;Gianguzza et al 2009Gianguzza et al , 2016Rassweiler, Schmitt & Holbrook 2010;Lane 2012;Urriago, Himmelman & Gaymer 2012;Galasso et al 2015) that may be modified by temperature variations. For example predation rate of the polar starfish Odontaster validus is compromised by high-temperature stress (Peck et al 2008;Kidawa, Potocka & Janecki 2010). Temperate regions routinely undergo wide temperature oscillations, due to seasonal cycles and temperature anomalies (Miller et al 1994;Hobday et al 2016), such as during ENSO events.…”
Section: Introductionmentioning
confidence: 99%